El juego como estrategia metodológica y su incidencia en el proceso de socialización de los niños y niñas del primer grado de educación básica, de la escuela Simón Bolívar, del cantón Celica, provincia de Loja. Período 2013-2014. Lineamientos alternativos - Salinas Pineda, Gladys Celeste (2015)
THE GAME AS A METHODOLOGICAL STRATEGY AND ITS IMPACT ON THE PROCESS OF SOCIALIZATION OF CHILDREN IN THE FIRST GRADE OF BASIC EDUCATION, SIMON BOLIVAR SCHOOL, CANTON CELICA, LOJA PROVINCE. 2013-2014. GUIDELINES ALTERNATIVE ", is a matter of this investigation, the overall objective was to develop a study on the use of play as a methodological strategy identifying levels of the investigated domain. As scientific methods, hypothetical, inductive, deductive, analytical and synthetic from the identification and description of the problem, objectives approach, analyzing bibliographic references, apply tools, process and analyze data, applied as an instrument structured observation sheet used on used game types and manifestations of socialization of the investigation. The theoretical framework discusses the game as a methodological strategy, evolution, types, importance, elements and characteristics; the socialization process: definition, indicators, family and school as socializing agents. As research results identified that 86.5% use the game of construction, 83.8% game manipulation, 75.7% the set of rules and symbolic; Regarding the process of socialization attachment behavior and acceptance has implications with 91.89%, the behavior of friendship with 86.48%, social cohesion and social relations with 72.97%, identity and self-concept 56.75 %, self-control and autonomy with 51.35%. It is concluded that if teachers use the game as a methodological strategy; the socialization process is excellent and very good. It is recommended to apply the alternative guidelines proposed to participate in recreation and socialization process of individual and collective behavior